Do randomised controlled trials evaluating functional outcomes following botulinum neurotoxin-A align with focal spasticity guidelines? A systematic review. Issue 26 (18th December 2022) - Sutherland, Edwina; Hill, Bridget; Singer, Barby J.; Ashford, Stephen; Hoare, Brian; Hastings-Ison, Tandy; Fheodoroff, Klemens; Berwick, Steffen; Dobson, Fiona; Williams, Gavin
Abstract: Purpose: The impact of botulinum neurotoxin-A (BoNT-A) on functional outcomes when managing focal muscle spasticity remains unclear. It is possible that randomised controlled trial (RCT) design and/or reporting may be a contributing factor. The objective of this review was to determine the extent to which RCTs evaluating functional outcomes following BoNT-A align with focal spasticity guidelines. Materials and methods: RCTs published from 2010 were included if they targeted focal spasticity, included BoNT-A, randomised a physical intervention to the upper/lower limb, or the primary outcome(s) related to the activity/participation domains of the International Classification of Functioning, Disability, and Health. Data extraction and quality appraisal using the Modified PEDro and Modified McMasters Tool were performed independently by two reviewers. General research practices were also extracted such as compliance with therapy reporting guidelines. Results: Fifty-two RCTs were eligible. Individualised goal setting was uncommon (25%). Six studies (11.5%) included multi-disciplinary management, and five (9.6%) included patient/caregiver education. Four studies (7.7%) measured outcomes beyond 6 months. The Median Modified PEDro score was 11/15. Conclusions: Alignment with focal spasticity guidelines in RCTs was generally low. Our understanding of the impact of focal spasticity management on functional outcomes may be improved if RCT design aligned more closely with guideline recommendations. IMPLICATIONS FOR REHABILITATION: The influence of BoNT-A on improved functional outcomes is yet to be determined. Individualised goal setting with a multi-disciplinary team is uncommon in an RCT design, despite it being a key guideline recommendation. Given the long-term nature of spasticity management, guidelines recommend short as well as long-term reviews following intervention however RCTs rarely assess beyond 6 months.